Pengaruh Gaya Kepemimpinan Demokratis, Komitmen Afektif dan Disiplin Kerja terhadap Kinerja pada Dinas Kesehatan Kota Yogyakarta - Wona Awang, John Gilbert Arfid; Prayekti, Prayekti; Hartanto, Selamet (Universitas Batanghari, 2024)
This research aims to determine the influence of Democratic Leadership Style (X1), Affective Commitment (X2), and Work Discipline (X3) on Performance (Y). This research is quantitative research. The research population was all employees of the Dinas Kesehatan Kota Yogyakarta, totaling 53 employees. The research sample was the entire population of 53 employees of the Dinas Kesehatan Kota Yogyakarta. The data collection technique uses a questionnaire. The data analysis technique uses descriptive statistical analysis, classic assumption tests consisting of normality, multicollinearity and hetercedasticity tests, and multiple regression tests. Sampling used a purposive sampling technique, and data collection was carried out using a survey method by distributing questionnaires. The data was processed using the SPSS version 25 application by carrying out data quality tests, classical assumption tests, multiple regression tests, t tests and coefficient of determination tests. Based on the test results in this research, it shows that the variables Democratic Leadership Style, Affective Commitment, and Work Discipline each have a significant effect on the performance of employees of the Dinas Kesehatan Kota Yogyakarta